MST567 - Categorical Data Analysis February 2021 - PPSM, Pusat Pengajian Sains Matematik (Pusat Pengajian Sains Matematik, 2021)
Please check that this examination paper consists of ELEVEN (11) pages of printed material before you begin the examination. Instructions : Answer EIGHT (8) questions.